The Biological Properties of Co-Doped Monetite Are Influenced by Thermal Treatment - de Almeida, Gerson Santos [UNESP]; Suter, Luisa Camilo [UNESP]; Pinto, Thais Silva [UNESP]; Carra, Maria Gabriela Jacheto [UNESP]; da Silva Feltran, Géorgia [UNESP]; de Moraes, Julia Ferreira [UNESP]; Corrêa, Diego Rafael Nespeque [UNESP]; Saeki, Margarida Juri [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP]; Zambuzzi, Willian Fernando [UNESP] (Wiley, 2025)
Calcium phosphates, notably monetite, are valued biomaterials for bone applications owing to their osteogenic properties and rapid uptake by bone cells. This study investigates the enhancement of these properties through Cobalt doping, which is known to induce hypoxia and promote bone cell differentiation. Heat treatments at 700°C, 900°C, and 1050°C are applied to both monetite and Cobalt-doped monetite, facilitating the development of purer, more crystalline phases with varied particle sizes and optimized cellular responses. Comprehensive physicochemical characterization through XRD, FTIR, Raman, SEM/EDS, and ASAP analyses shows significant phase transformations into pyrophosphate, influencing the materials' structural and functional attributes. When utilized to condition a culture medium for MC3T3-E1 cells, these materials demonstrate non-cytotoxic behavior and provoke specific gene responses associated with the osteoblastic phenotype, angiogenesis, adhesion, and extracellular matrix remodeling. Significantly, non-heat-treated Cobalt-doped Monetite retains properties advantageous for clinical applications such as dental and orthopedic implants, where lower processing temperatures are crucial. This attribute, combined with the material's straightforward production, highlights its practicality and potential cost-effectiveness. Further research is essential to assess the long-term safety and efficacy of these materials in clinical settings. Our findings underscore the promising role of Cobalt-doped Monetite in advancing bone repair and regeneration, setting the stage for future innovations in treating bone lesions, enhancing implant integration, and developing advanced prosthetic coatings within the field of tissue engineering.
Keywords: biomaterials availability; bone remodeling; calcium phosphate(s); cell culture; smart materials